Differences in baseline and post-season King-Devick times between recreational and competitive youth soccer players - Ugo Bitussi S; Candice Osborne; Shannon Juengst; Bert Vargas; Cindy Dolezal; Steven Avers; Christopher Ha; Nicholas Elkins; Kathleen Bell (Archives of Sports Medicine and Physiotherapy - Peertechz Publications, 2019)
Objective: To determine if K-D scores differed between competitive youth soccer players and recreational youth soccer players ages 8-12. Design: Prospective cohort study during the spring and fall soccer seasons of 2017. Participants were 8-12 years of age and were enrolled in recreational or competitive soccer.  Methods: Participants performed the K-D test before the first practice of the soccer season and during the last two weeks of the season. The main outcome measure was the time required to complete the K-D test before and after the soccer season in participants without a positive K-D screening for concussion.  Results: Forty participants (19 competitive and 21 recreational) completed the study. The pre-season recreational players (66.04s, SD = 15.22s) vs competitive players (59.88s, SD = 13.94s) had a mean difference of 6.16s (Z = .96, p = .34). The post-season recreational players (60.45s, SD = 13.46) vs competitive players (50.50s, SD = 8.49) had a mean difference of 9.95s (Z = 2.31, p = .02).  Conclusions: Level of play may influence performance on the K-D. Future studies of visual efficiency in youth athletes may also provide insight into differences in performance of the K-D.